2019
DOI: 10.1186/s12929-019-0587-9
|View full text |Cite
|
Sign up to set email alerts
|

The functional roles of IGF-1 variants in the susceptibility and clinical outcomes of mild traumatic brain injury

Abstract: BackgroundInsulin-like growth factor 1 (IGF-1) is an important pleiotropic hormone that exerts neuroprotective and neuroreparative effects after a brain injury. However, the roles of IGF-1 variants in mild traumatic brain injury (mTBI) are not yet fully understood. This study attempted to elucidate the effects of IGF-1 variants on the risk and neuropsychiatric outcomes of mTBI.MethodsBased on 176 recruited mTBI patients and 1517 control subjects from the Taiwan Biobank project, we first compared the genotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…According to the clinical studies, 80–90% of all TBI cases are mild (mTBI) but have significant delayed consequences and therefore are a serious problem of modern healthcare. The symptoms of mTBI in the acute phase are usually transient and subtle for the patient himself, however, in some cases, they can be accompanied by a long-term inflammatory process with a delayed outcome in cognitive dysfunction of varying severity 2 , 3 . Lack of proper and timely therapeutic treatment of mTBI can trigger such pathological conditions and processes as chronic neuroinflammation, oxidative stress, axonal damage, impaired cognitive functions 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the clinical studies, 80–90% of all TBI cases are mild (mTBI) but have significant delayed consequences and therefore are a serious problem of modern healthcare. The symptoms of mTBI in the acute phase are usually transient and subtle for the patient himself, however, in some cases, they can be accompanied by a long-term inflammatory process with a delayed outcome in cognitive dysfunction of varying severity 2 , 3 . Lack of proper and timely therapeutic treatment of mTBI can trigger such pathological conditions and processes as chronic neuroinflammation, oxidative stress, axonal damage, impaired cognitive functions 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that IGF-1rs978458 plays a more complex and important role in the etiology of MDD. Wang et al [38] showed that patients carrying minor allele of rs972936 showed more dizziness and multiple neuropsychiatric symptoms including depression after mild traumatic brain injury. This is inconsistent with our results, which may be due to the different research objects.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of IGF-1 stimulates the downstream signaling in the post-TBI brain [ 94 ]. Moreover, Wang et al documented that the administration of IGF-1 variants correlated with the vulnerability and the neuropsychiatric outcome of post-TBI patients [ 95 ]. Of note, IGF-1 activates intracellular signaling by enhancing the pathways-phosphatidylinositol 3-kinase/ protein kinase B (PI3K/Akt) and mitogen-activated protein kinase/ extracellular signal-regulated kinase (MAPK/ERK), which play pivotal roles, such as managing glucose utilization, neurogenesis, synaptic plasticity and angiogenesis [ 96 ].…”
Section: Novel Pharmacologic Strategies For Tbi: From Experimental To...mentioning
confidence: 99%